2022
DOI: 10.1265/ehpm.21-00018
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in the association of physical leisure activities with incident disability among community-dwelling older adults

Abstract: Background The relationship between leisure activities (LA) in old age and prevention of disability has not been fully investigated, and age and gender differences of these relationships are unknown. This study aimed to investigate whether physical and cognitive LA predicted incident disability among community-dwelling older adults by age and gender. Methods We prospectively observed 8,275 residents aged 65 or above without disability at baseline for 3 years. Incident d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It has been reported that among Japanese people aged 60 and older, the proportion of Internet users is higher in men than in women, and decreases with age [ 27 ]. Previous studies of community-dwelling older people in Japan reported that the risk of developing incident disability was higher in women than in men, and increased with age [ 3 , 28 ]. Because the association between the frequency of Internet use and incident disability may differ by age and gender, we conducted stratified analyses by age or gender.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that among Japanese people aged 60 and older, the proportion of Internet users is higher in men than in women, and decreases with age [ 27 ]. Previous studies of community-dwelling older people in Japan reported that the risk of developing incident disability was higher in women than in men, and increased with age [ 3 , 28 ]. Because the association between the frequency of Internet use and incident disability may differ by age and gender, we conducted stratified analyses by age or gender.…”
Section: Methodsmentioning
confidence: 99%
“…In countries, including Japan, where the aging of the population is progressing rapidly, preventing older people from requiring long-term care is an urgent issue to address, in order to ensure the sustainability of the social security system. Numerous studies have reported that social participation in old age is associated with a lower risk of developing disability [ 1 3 ]. This is because through social participation, older people can connect with other people, increase their physical activity, receive intellectual stimulation, and have a sense of purpose in life, which helps prevent deterioration of mental and physical functions.…”
Section: Introductionmentioning
confidence: 99%